Rethinking Leadership: Finding the Right Balance in Managing the 21st Century Library - Mishra, Champeswar (2012)
Library must strike an appropriate balance in providing innovative and quality service to the users. Library should stay focus on customers and their changing needs and should create library as service rather than library as place of collection. Professionals in libraries will have to learn to lead change and rethink their strategic role to find out the gap between patron demands and service and should fill the gap by apply strategic ideas. A strong, dynamic, and visionary leadership is the need of the hour in order to preserve the past, convene the present and work to build a better future. If library wish to sustain, remain competitive and viable, transformational and evidence based library leadership must developed among the library leaders to sustain and thrive to build a successful libraries of the future. This paper will examine and explore the new frontiers of library leadership and enthusiastically implement strategic action plans for sustaining and maintaining the library of the future with special emphasizes on core competencies for the next decade librarians.